Reality Status Judgments of Real and Fantastical Events in Children’s Prefrontal Cortex: An fNIRS Study - Li, Hui; Liu, Tao; Woolley, Jacqueline D.; Zhang, Peng (Frontiers in Human Neuroscience, 2019)
The present study aimed to examine neural mechanisms underlying the ability to differentiate reality from fantasy. Using functional near-infrared spectroscopy (fNIRS), we measured prefrontal activations in children and adults while they performed a reality judgment task. Participants’ task was to judge the reality status of events in fantastical and realistic videos. Behavioral data revealed that, although there was no accuracy difference, children showed significantly longer reaction times in making the judgments than did adults. The fNIRS data consistently revealed higher prefrontal activations in children than in adults when watching the videos and judging the reality of the events. These results suggest that when making judgments of event reality, children may require more cognitive resources and also mainly rely on their own personal experiences.